2007
DOI: 10.1051/ebr:2007006
|View full text |Cite
|
Sign up to set email alerts
|

Long term evaluation of field-released genetically modified rhizobia

Abstract: This is the report of the first open field release of genetically modified microorganisms (GMMs) in Italy. It covers ten years of monitoring, and follows in-field GMM dynamics from strain release to disappearance below detection limits, as well as assessment of impact on resident microorganisms. The bacteria released belong to the nitrogen fixing legume endosymbiont Rhizobium leguminosarum bv. viciae, and were engineered with non-agronomically-proficient traits, in order to assess their behavior and fate witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Currently, we have methods to predict and test the environmental impact of an engineered microbe on indigenous microbial populations in soil (Corich et al, 2007; reviewed in Urgun-Demirtas et al, 2006). However, this work is limited to a few representative cases.…”
Section: Risk Analysis In Synthetic Biologymentioning
confidence: 99%
“…Currently, we have methods to predict and test the environmental impact of an engineered microbe on indigenous microbial populations in soil (Corich et al, 2007; reviewed in Urgun-Demirtas et al, 2006). However, this work is limited to a few representative cases.…”
Section: Risk Analysis In Synthetic Biologymentioning
confidence: 99%
“…Introduced strains are often poor competitors and populations never recover from the initial drop (Corich et al 2007;Hirsch and Spokes 1994). However, even small populations continue to affect the rhizosphere.…”
Section: Effects On Indigenous Microorganismsmentioning
confidence: 99%
“…Corich et al (2007) found that stability of a genetic marker ranged from 85 to 100 % over the course of a growing season in a field study of R. leguminosarum and pea. Transfer of genetically modified traits to autochthonous microorganisms would be predicted to occur, but has rarely been observed in practice .…”
Section: Effects On Indigenous Microorganismsmentioning
confidence: 99%
“…The importance of microbe-tracking and rescuing protocols has also been stressed at political level in Europe, through the guidelines issued at both EU and national levels . Long-term approaches on risk assessment have been undertaken through joint programs, which have yielded comprehensive data covering several fields (Jansson et al, 2000;Nuti et al, 2003;Corich et al,. 2007).…”
Section: Introductionmentioning
confidence: 99%